Anti-inflammatory activities of christia vespertilionis protease and palm tocotrienol-rich fraction in carrageenan-induced BALB/c paw oedema / Izzah Farhah Zambari ... [et al.] - Zambari, Izzah Farhah; Mohamad Aini, Maliya Azilah; Norisam, Irmaliayana; Iran, Nabiha; Abdul Hafid, Sitti Rahma; Muhamad, Nur Airina (Faculty of Pharmacy, 2024)
Inflammation is a common ailment that could develop into a chronic disease such as cancer, diabetes and rheumatoid if not cured early. Commonly, synthetic drugs such as aspirin are used to cure inflammation. However, synthetic drugs could have adverse side effects with long-term consumption. This study investigates the anti-inflammatory activities of Christia vespertilionis protease (CVP) and palm tocotrienol-rich fraction (TRF) in carrageenan-induced BALB/c paw oedema. Carrageenan was injected into the left hind paw of BALB/c mice, generating an acute inflammatory response due to the induction of neutrophils. Inflammatory mediators such as tumour necrosis factor-alpha (TNF-α), interleukin-6 (IL-6) and free radical nitric oxide (NO) were determined by enzyme-linked immunosorbent assay (ELISA). All parameters of inflammation such as paw size (%), amount of TNF-α (pg/mg), amount of IL-6 (pg/mg) and level of nitric oxide (µM), decreased through the treatments of CVP, TRF, a combination of CVP and TRF (CVP+TRF) and aspirin. The treatments were shown to be effective against inflammation, particularly CVP+TRF compared to aspirin, which could provide a novel therapeutic approach to inflammatory diseases.